Application of foreign law - Esplugues Mota, Carlos; Iglesias, José Luis; Palao Moreno, Guillermo (Sellier European Law Pub., 2011)
During the last decade Europe has undertaken an active and broad process of harmonisation of choice-of-law rules within the EU. However, this drastic movement towards a harmonised system has so far left aside a highly relevant issue: the application by judicial and non-judicial authorities of the foreign law. In full contrast to the little attention so far paid to it in the EU, this issue is said to be the crux of the conflict of laws. It violates legal certainty and contradicts the objective of ensuring full access to justice to all European citizens within the EU. This book provides a comparative study of the existing situation in all EU member states and drafts some basic principles for a future European instrument. It will become a highly useful tool for lawyers, judges, notaries, land registries, academics, prosecutors etc.